Criminal Acts Against Indonesian Migrant Workers : A Study on Law Enforcement and Legal Protection - Gabriel Simson Tamba; Revo Christanto; Fadlan Fadlan; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the complex challenges surrounding criminal acts perpetrated against Indonesian migrant workers and evaluates the effectiveness of current law enforcement mechanisms and legal protection frameworks. The research analyzes both domestic and international legal instruments designed to protect migrant workers, with particular focus on their implementation and practical outcomes. Through a comprehensive assessment of case studies, legal documents, and enforcement data, this study reveals significant gaps between established legal protections and their actual enforcement. Key findings indicate that Indonesian migrant workers frequently face various forms of criminal exploitation, including physical abuse, fraud, human trafficking, and unlawful confinement, while working abroad. The study identifies several systemic barriers to effective legal protection, including jurisdictional complexities, limited access to legal resources, inadequate bilateral agreements, and weak enforcement mechanisms in both sending and receiving countries. Furthermore, the research highlights the critical role of government agencies, diplomatic missions, and non-governmental organizations in providing legal assistance to victimized workers. The study concludes by proposing concrete recommendations for strengthening the legal protection framework, enhancing international cooperation in law enforcement, improving access to justice for migrant workers, and developing more robust preventive measures against criminal exploitation.